EFEKTIVITAS PELAKSANAAN FUNGSI KELOMPOK SIAGA BENCANA (KSB) KELURAHAN BUNGO PASANG DALAM MENINGKATKAN KESIAPSIAGAAN UNTUK MENGHADAPI BENCANA - varisa kenia valery; Zikri Alhadi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
ABSTRACT Indonesia is one of the disaster-prone countries, where the city of Padang is included. Padang City's topography which has very varied characteristics makes Padang City vulnerable to disasters. Based on data from the Central Statistics Agency of the City of Padang the number of Sub-districts in the City of Padang is as much as 11 Sub-districts and the number of village in the City of Padang is as many as 104 village. From the Padang City RPB data, the level of disasters in the city of Padang varies. One of the villages that are prone to disasters is the Bungo Pasang Village, so to improve the preparedness of the Bungo Pasang Village in the form of a Disaster Preparedness Group (KSB) of the Bungo Pasang Village in 2011. However, currently the function of the Bungo Pasang Village KSB has not run optimally. , where there are still some obstacles faced by members of the KSB village Bungo Pasang. This study aims to determine the effectiveness of the implementation of the function of the Disaster Preparedness Group (KSB) of Bungo Pasang Village in improving preparedness to deal with disasters. This type of research is descriptive qualitative, where sources of data are taken through secondary data and primary data. Data collection techniques in the form of observation, interviews, and documentation. Keywords: Disasters, implementation of Disaster Preparedness Group functions